PENGARUH ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA UMKM BIDANG KULINER DI YOGYAKARTA - Dwi Wahyu Pril Ranto (Jurnal Bisnis, Manajemen, dan Akuntansi, 2016)
The purpose of this study is to examine partial affect and simultaneous variablesentrepreneurial orientation consisting of the dimensions innovativeness, risk taking andproactiveness towards performance micro small and medium enterprises (SMEs) in the culinary.The population in this study is SMEs in the culinary is located in Bantul, precisely SMEsthat are around the campus in UMY, ALMA ALTA, STIKES Ayani and BSI. Reasons sampling atthis location because there are many SMEs in the location form stall engaged in the culinary andculinary activities in this are growing rapidly. The purposive sampling is used in this research withsample criteria that SMEs in the culinary has one year running the business.Based on hypothesis testing using multiple regression showed that the variablessimultaneously and parsial variable entrepreneurial orientation consisting of the dimensionsinnovativeness, risk taking and proactiveness significantly affect the performance of SMEs.Keywords : entrepreneurial orientation, innovativeness, risk taking, proactiveness, businessperformance